Reification of religious figures in azab genre religious sinetron: An interpretative phenomenological analysis - Haroni, Nanang; Arianti, Gusmia; Weaham, Muhammadroflee; Hamid, Abdul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - To examine the phenomenon of reification in the presence of religious figures in Indonesian